Functions of social networks in maternal food choice for children in Mexico. Issue 1 (10th September 2021) - Reyes, Ligia I.; Frongillo, Edward A.; Moore, Spencer; Blake, Christine E.; Gonzalez, Wendy; Bonvecchio, Anabelle
Abstract: Food choice for children has important implications in establishing early‐life dietary habits and preferences. Food choice for children has been studied as parent–child dyad dynamics, but little is known about the extended system of relationships in maternal food choice for children. The objective of this study was to understand the functions of mothers' social networks in the food choices that mothers make for their children ages 1 to 5 years old in rural Mexico. In‐depth interviews were conducted with 46 participants in three rural communities. The interviews inquired about participants' child‐feeding practices, personal and local beliefs about child feeding and the individuals with whom they had conversations about food and child feeding. All interviews were conducted in Spanish, audio‐recorded, transcribed verbatim, verified for quality and analysed using the constant comparative method. Five interconnected networks emerged, consisting of household family, non‐household family, community, children's initial school and health and nutritional programme personnel. Each network had functions in food choice that ranged from shared food decision‐making in the household family network to imparting formal dietary guidance in the health and nutritional programme personnel network. Across the networks, professionals, participants' mothers and mothers‐in‐law, community senior women and other women with children emerged as prominent figures whom participants would turn to for child‐feeding advice. These findings provide empirical evidence that social networks, as an organized system of interconnected relationships, have vital functions in establishing social norms for food choices made for children that can be leveraged to promote healthy food choices.